Coexistence of blaIMP-4, blaNDM-1 and blaOXA-1 in blaKPC-2-producing Citrobacter freundii of clinical origin in China - Qiao, Jie; Chen, Yingying; Ge, Haoyu; Xu, Hao; Guo, Xiaobing; Liu, Ruishan; Li, Chenyu; Chen, Ruyan; Gou, Jianjun; Chen, Mantao; Zheng, Beiwen (Frontiers in Microbiology, 2023)
Purpose To explore the genetic characteristics of the IMP-4, NDM-1, OXA-1, and KPC-2 co-producing multidrug-resistant (MDR) clinical isolate, Citrobacter freundii wang9. Methods MALDI-TOF MS was used for species identification. PCR and Sanger sequencing analysis were used to identify resistance genes. In addition to agar dilution, broth microdilution was used for antimicrobial susceptibility testing (AST). We performed whole genome sequencing (WGS) of the strains and analyzed the resulting data for drug resistance genes and plasmids. Phylogenetic trees were constructed with maximum likelihood, plotted using MAGA X, and decorated by iTOL. Results Citrobacter freundii carrying blaKPC-2, blaIMP-4, blaOXA-1, and blaNDM-1 are resistant to most antibiotics, intermediate to tigecycline, and only sensitive to polymyxin B, amikacin, and fosfomycin. The blaIMP-4 coexists with the blaNDM-1 and the blaOXA-1 on a novel transferable plasmid variant pwang9-1, located on the integron In1337, transposon TnAS3, and integron In2054, respectively. The gene cassette sequence of integron In1337 is IntI1-blaIMP-4-qacG2-aacA4′-catB3Δ, while the gene cassette sequence of In2054 is IntI1-aacA4cr-blaOXA-1-catB3-arr3-qacEΔ1-sul1. The blaNDM-1 is located on the transposon TnAS3, and its sequence is IS91-sul-ISAba14-aph (3′)-VI-IS30-blaNDM-1-ble-trpF-dsbD-IS91. The blaKPC-2 is located on the transposon Tn2 of plasmid pwang9-1, and its sequence is klcA-korC-ISkpn6-blaKPC-2-ISkpn27-tnpR-tnpA. Phylogenetic analysis showed that most of the 3400B0C. freundii isolates from China were divided into three clusters. Among them, wang1 and wang9 belong to the same cluster as two strains of C. freundii from environmental samples from Zhejiang. Conclusion We found C. freundii carrying blaIMP–4, blaNDM–1, blaOXA-1, and blaKPC-2 for the first time, and conducted in-depth research on its drug resistance mechanism, molecular transfer mechanism and epidemiology. In particular, we found that blaIMP-4, blaOXA-1, and blaNDM-1 coexisted on a new transferable hybrid plasmid that carried many drug resistance genes and insertion sequences. The plasmid may capture more resistance genes, raising our concern about the emergence of new resistance strains.